La possibilité d’une île : la mythologie du Bronx, archipel enchanté, dans trois textes autobiographiques de Jerome Charyn - Sophie Vallas (Anglophonia)
Jerome Charyn recently published an autobiographical trilogy (The Dark Lady from Belorusse, 1997; The Black Swan, 2000 and Bronx Boy, 2007) in which the main focus, more than his adored and fascinating mother at the heart of the story, more than Charyn’s childhood and adolescence, is the Bronx. The Bronx is the neighborhood in which Charyn grew up and learnt about life the hard way, but also a haunting place in his whole work. This paper proposes to see Charyn’s nostalgic painting of the Bronx in the 1940s first as a historically documented evocation, but also as a mythologizing enterprise: as the reader follows Charyn from one mythical landmark to the next, he realizes that an imaginary geography, a magical cartography of the Bronx are being drawn before his eyes while a powerful Melvillian intertext puts the final touches to the recollection of an "evilly enchanted ground". The Bronx appears as an isolated, self-reliant archipelago reconstructed by distance, memory and mythopsychosis.